MEASURE OF FREQUENCY OF ALVEOLAR OSTEITIS USING TWO DIFFERENT METHODS OF OSTEOTOMY IN MANDIBULAR THIRD MOLAR IMPACTIONS: A DOUBLE-BLIND RANDOMIZED CLINICAL TRIAL - Rashid, Hina; Hussain, Azmina; Sheikh, Abdul Hafeez; Azam, Kehkishan; Malik, Sofia; Amin, Muhammad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Dento-alveolar surgical procedures involving third molar teeth are the most common surgical procedure in the field of surgery. The objective of this research was to analyse the impact of surgery on the incidence of alveolar osteitis after surgical removal of mandibular third molar and to compare two different bone cutting methods following impacted mandibular third molar surgery. Methods: This double blinded randomized clinical trial was executed at the OPD of Department of Oral and Maxillofacial Surgery, Dow University of Health Sciences, Karachi. The study duration was four months. It was conducted on 60 patients needing unilateral mandibular third molar impaction removal. Patients were randomized to two groups (i.e., physio dispenser group and slow speed handpiece group) before surgery. The surgical procedure was performed under local anaesthesia by using standardized cross infection protocol. The frequency of alveolar osteitis was evaluated on third-day postoperatively. Alveolar osteitis was diagnosed and confirmed by patient’s history and clinical evaluation. Post-operative sequelae were observed and recorded objectively. Results: Out of 60 patients’, five patients experienced alveolar osteitis, and the incidence rate was 8.3%. A significant p-value of 0.000 was calculated using binomial test for comparison of alveolar osteitis among both groups. Inter-examiner reliability was assessed by kappa and good (62%) agreement, which was found among the examiners, who diagnosed alveolar osteitis clinically. Post-operative sequelae were insignificant in slow speed hand piece group. Conclusion: It was observed that alveolar osteitis was reported in physio-dispenser group; similarly, post-operative complications were also more in this group as compared with slow speed-hand piece group. No surgical complications were observed in slow speed-hand piece group suggesting slow speed hand piece mode of osteotomy to be safer for third molar extraction as compared with physio-dispenser. Keywords: Alveolar Osteitis; bone cutting; mandibular third molar surgery